Anatomical Variations in Meniscal Horn Attachments in the North Indian Population: A Comprehensive Cadaveric Analysis - Beniwal, Sonia; Ravi, Kumar Satish; Singla, Mukesh; Kalia, Roop Bhushan (Journal of Neonatal Surgery, 2025)
We undertook a detailed examination of the attachment points of the meniscal horns in a North Indian cadaver sample, analyzing thirty knees to map the diverse ways they connect to bone and ligaments. What we found was significant anatomical variation, notably in the anterior horn of the medial meniscus. Three main attachment types emerged: Type III, which attaches to the anterior tibial plateau slope, was the most common (almost 47%), followed by Type I, which attaches to the flat intercondylar area (40%), and finally Type II, which hooks onto the medial articular plateau (around 13%). It's worth noting that these patterns seem to differ significantly from what has been observed in previous studies of Ghanaian, Kenyan, and Caucasian populations, offering key information for surgeons, radiologists, and anatomists who work with North Indian patients. It is important to state that this population specificity could have major implications